2022
DOI: 10.1016/j.bja.2021.08.034
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of perioperative pharmacological and regional pain interventions in adult spine surgery: a network meta-analysis and systematic review of randomised controlled trials

Abstract: Background: Development of a widely accepted standardised analgesic pathway for adult spine surgery has been hampered by the lack of quantitative analysis. We conducted a systematic review and network meta-analysis (NMA) to compare, rank, and grade all pharmacological and regional interventions used in adult spine surgery. Methods: A systematic search was performed in January 2021. We performed double study screening, selection, and data extraction. The co-primary outcomes were cumulative morphine consumption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…These researchers also found the efficacy of analgesia to increase in a graded manner with additional multimodal drugs used. 27 Similarly, Cozowicz et al 37 found use of NSAIDs and COX-2 inhibitors in the perioperative period to be associated with significantly reduced prescriptions of opioid, decreased LOS, and decreased cost for patients undergoing posterior lumbar fusion surgery. Additional studies identified preoperative celecoxib in addition to gabapentin to result in significant decreases in postoperative pain and opioid consumption in elective spinal fusion 34 and laminectomy 35 patients, which was not seen with gabapentin alone.…”
Section: Nsaids and Selective Cox-2 Inhibitorsmentioning
confidence: 99%
See 3 more Smart Citations
“…These researchers also found the efficacy of analgesia to increase in a graded manner with additional multimodal drugs used. 27 Similarly, Cozowicz et al 37 found use of NSAIDs and COX-2 inhibitors in the perioperative period to be associated with significantly reduced prescriptions of opioid, decreased LOS, and decreased cost for patients undergoing posterior lumbar fusion surgery. Additional studies identified preoperative celecoxib in addition to gabapentin to result in significant decreases in postoperative pain and opioid consumption in elective spinal fusion 34 and laminectomy 35 patients, which was not seen with gabapentin alone.…”
Section: Nsaids and Selective Cox-2 Inhibitorsmentioning
confidence: 99%
“…Regardless of mechanism, acetaminophen is reported to be safe and effective as a single agent or combination agent with opioids at a dose of less than 4 g per day in patients not contraindicated due to severe hepatic impairment or previous sensitivity 26. Studies of MMA protocols within spine surgery have routinely isolated acetaminophen as one of the active agents in successful MMA protocols 2,27–29…”
Section: Classes and Mechanisms Of Multimodal Analgesiamentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, in a large, observational, multicenter study, spine surgery induced severe postoperative pain and was ranked the second (spinal fusion one to two segments) and third (dorsal spinal fusion, three or more segments) most painful surgical act among 179 procedures 5. In this context, a multimodal analgesic approach has recently been recommended to enhance postoperative rehabilitation and pain relief after spine surgery 6–8…”
Section: Introductionmentioning
confidence: 99%